Association of Carcinoembryonic Antigen, Hemoglobin, and Neutrophil to Lymphocyte Ratio with Colorectal Cancer Histopathological Grade in West Sumatra, Indonesia - Muhammad Zidane Innanda; Dwi Yulia; Avit Suchitra; Wirsma Arif Harahap; Rikarni Rikarni; Eka Nofita (Jurnal Kesehatan, 2026)
Colorectal cancer is a global health issue with a significant incidence and mortality rate. Identifying clinical characteristics using tumor biomarkers and hematological parameters is a crucial aspect in evaluating tumor cell differentiation grade. This study aims to determine the characteristics of Carcinoembryonic Antigen (CEA) levels, hemoglobin, and Neutrophil to Lymphocyte Ratio (NLR) values as indicators of histopathological differentiation grade in colorectal cancer patients. This was an observational, analytic study with a retrospective design, using medical record data from patients at Dr. M. Djamil General Hospital in Padang, from January 2023 to December 2024. A total of 154 patients meeting the inclusion and exclusion criteria were selected using a total sampling technique. Data were analyzed using statistical tests to assess the significance of the relationship between variables. The patient distribution showed a higher prevalence of females (55.8%), and more than half (62.3%) were aged 50 years or older. The histopathological profile was predominantly low grade (81.2%). Statistical test results showed a significant association between CEA levels and histopathological differentiation grade (p=0.017). However, no statistically significant association was found between hemoglobin levels (p=0.822) or NLR values (p=0.303) and histopathological differentiation grade. There is a potential association between CEA levels and histopathological differentiation grade, whereas hemoglobin levels and NLR values did not show a significant association. CEA levels can serve as a potential indicator in predicting tumor differentiation grade in colorectal cancer patients.